2015
DOI: 10.1016/j.devcel.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A Generic and Cell-Type-Specific Wound Response Precedes Regeneration in Planarians

Abstract: Summary Regeneration starts with injury. Yet how injuries affect gene expression in different cell types, and how distinct injuries differ in gene expression remains unclear. We defined the transcriptomes of major cell types of planarians – flatworms that regenerate from nearly any injury – and identified 1,214 tissue-specific markers across 13 cell types. RNA sequencing on 619 single cells revealed that wound-induced genes were either expressed in nearly all cell types or specifically in one of three cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
371
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(403 citation statements)
references
References 57 publications
(107 reference statements)
28
371
3
1
Order By: Relevance
“…Congruent with our previous results, single-cell RNA sequencing (scRNAseq) [13,27] of stem and differentiated tissues demonstrated that yki was not enriched in any of the stem cell sub-classes (γ, z or σ), and instead, was primarily expressed in differentiated tissues, such as the epidermis, muscle, and gut (S1D Fig) [22]. Interestingly, these same differentiated tissues have recently been shown to be enriched for the expression of wound-induced genes, collectively known as the "transcriptional injury response" [13].…”
Section: Yorkie Restricts Stem Cell Proliferation During Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Congruent with our previous results, single-cell RNA sequencing (scRNAseq) [13,27] of stem and differentiated tissues demonstrated that yki was not enriched in any of the stem cell sub-classes (γ, z or σ), and instead, was primarily expressed in differentiated tissues, such as the epidermis, muscle, and gut (S1D Fig) [22]. Interestingly, these same differentiated tissues have recently been shown to be enriched for the expression of wound-induced genes, collectively known as the "transcriptional injury response" [13].…”
Section: Yorkie Restricts Stem Cell Proliferation During Regenerationmentioning
confidence: 99%
“…https://doi.org/10.1371/journal.pgen.1006874.g001 two waves of transcription: an immediate "early wave" that peaks in expression by~6 hpa, and; a subsequent "late wave" that lasts in expression until~24 hpa [12,13]. In yki(RNA), the early-wave marker fos-1, was precociously expressed at 0.5 hpa and was prolonged until 12 hpa (Fig 2A).…”
Section: Yorkie Restricts Stem Cell Proliferation During Regenerationmentioning
confidence: 99%
“…Not all wounds initiate regeneration, and the signals that convert a generic wound response to a regenerative process are unknown (Wurtzel et al, 2015;Owlarn and Bartscherer, 2016). Kerstin Bartscherer (MPI, Muenster, Germany) showed that by blocking wound-induced ERK activity in planarians, amputated animals close their wound but do not regenerate until ERK activity is restored, thereby dissociating these two processes.…”
Section: Wound Repair and Injury-induced Signalingmentioning
confidence: 99%
“…We could identify cells that co-expressed smedwi-1 and either β1-integrin or α-integrin-2, but the majority of FISH signal for these two genes was too disperse and punctate to assign readily to particular cells. Additionally, prior analyses found expression of these genes using RNA-seq to measure the transcriptome of FACS-sorted neoblasts as a bulk population (Labbe et al, 2012) and also in the transcriptomes of neoblasts as measured by single-cell RNA-seq, as well as expression in nonneoblast cells (Wurtzel et al, 2015) (Fig. S6F,G).…”
Section: Integrin Is Necessary For Neoblast and Neuronal Progenitor Lmentioning
confidence: 99%
“…Components or putative regulators of the ECM have been identified as expressed following injury in several regeneration models, including planarians (Wenemoser et al, 2012;Wurtzel et al, 2015), axolotl (Rao et al, 2009;Knapp et al, 2013) and sea anemone (DuBuc et al, 2014). However, the function of these in tissue assembly is unknown.…”
Section: Introductionmentioning
confidence: 99%